Empowering Engagement: Digital Community Marketing Strategies In The Era Of Interactive Platforms - Diana; Muhammad Haldy (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study explores the implementation of digital community marketing strategies as a means to strengthen customer engagement in the era of interactive platforms. The research highlights how digital communities serve as powerful ecosystems that enable brands to build trust, foster participation, and create meaningful relationships with consumers. Through the use of social media, online forums, and other interactive tools, companies can shift from transactional marketing to engagement-driven communication. The study employs a qualitative-descriptive approach by analyzing various case studies of successful digital community initiatives across industries. The findings reveal that active interaction, personalized content, and community empowerment are key drivers of customer loyalty and advocacy in the digital age. Ultimately, this research emphasizes that sustainable marketing success depends on the brand’s ability to nurture a sense of belonging and co-creation within its digital community.